Long-term neurological consequences following benzodiazepine exposure: A scoping review - Kyla N. Shade; Alexis D. Ritvo; Bernard Silvernail; A. J. Reid Finlayson; Jolene E. Bressi; D. E. Foster; Ian J. Martin; Christi Piper; Peter R. Martin (PLoS ONE, 2025)
Benzodiazepine acute withdrawal syndrome is well known, but the long-term neurological consequences of benzodiazepine exposure are much less familiar. A scoping review was conducted of electronic databases for studies that reported on patient outcomes four or more weeks after complete cessation of benzodiazepine use. Forty-six results were retrieved in total, some of which provided signals for protracted symptoms, often reported as incidental findings, and others that showed benzodiazepine discontinuation was beneficial. Some overlap occurred in the outcomes, but these two groups of studies suggest that the benefits of benzodiazepine discontinuation for many patients tended to obscure the more prolonged, severe, and sometimes debilitating symptoms that persisted for months and years in a subpopulation of patients. The prevalence or trajectory of these enduring symptoms could not be determined from these studies. Further elucidation of the potential neurotoxicity of benzodiazepines is needed to better understand protracted symptoms and their treatment. Clinicians, patients, and the healthcare system must be cognizant of the risks of benzodiazepine exposure beyond two to four weeks.